Analysis of Emotional Intelligence in the Learning Process of Elementary School Students - Melani Reviana; Andi Rafidah Nuraniyah; Devanya Mafaza (JEES: Journal of Education and Educational Sciences, 2025)
This study aims to analyze the structure of emotional intelligence among elementary school students using an Exploratory Factor Analysis (EFA) approach. A total of 240 students from grade 4 to grade 6 in some schools the basis of the state in the Cirebon City area was made sample study through stratified random sampling technique, to ensure representation based on level class, type gender, and group age. Instrument measurements used were developed based on the four model branch Mayer-Salovey-Caruso's capabilities, which include aspects perception emotions, management emotions, understanding to emotions, as well as the ability to use emotions in a constructive way. Data analysis was carried out using Partial Least Squares Structural Equation Modeling (PLS-SEM) method, which shows that all over construct own very good validity and reliability, indicated by the factor loading value > 0.70 and Average Variance Extracted (AVE) > 0.50. The Perceptions of Emotions dimension has the biggest contribution to construct emotional intelligence, while the Ability to Generate is the dimension with the lowest contribution. The findings underscore the need for contextual and accurate instruments to measure emotional intelligence in children as well as support the integration of emotional education into curriculum school bases in a systematic way.